The Progression of Celiac Disease, Diagnostic Modalities, and Treatment Options - Zahid Ijaz Tarar MD; Muhammad Usman Zafar MD; Umer Farooq MD; Omer Basar MD; Veysel Tahan MD; Ebubekir Daglilar MD (SAGE Publishing, 2021)
Celiac disease (CD) is an autoimmune disorder that affects genetically predisposed individuals who are sensitive to gluten and related proteins. It affects children and adults with increasing prevalence in the older age groups. Both adaptive and innate immune responses play role in CD pathogenesis which results in damage of lamina propria and deposition of intraepithelial lymphocytes. There are other proposed mechanisms of CD pathogenesis like gastrointestinal infections, intestinal microbiota, and early introduction of gluten. The diagnosis of CD is based on clinical symptoms and serological testing, though a majority of cases are asymptomatic, and small intestinal biopsies are required to confirm the diagnosis. Celiac disease is generally associated with other autoimmune diseases, and it is advisable to test these patients for diseases like type 1 diabetes mellitus, Addison's disease, thyroid diseases, inflammatory bowel disease, and autoimmune hepatitis. The patient with a new diagnosis of CD requires close follow-up after starting treatment to see symptom improvement and check dietary compliance. A newly diagnosed patient is advised to follow with a dietitian to better understand the dietary restrictions as about 20% of patients stay symptomatic even after starting treatment due to noncompliance or poor understanding of diet restrictions. The most effective treatment for CD is a gluten-free diet, but work on non-dietary therapy is in process and few medications are in the clinical trial phase.